Study of interferon-β antiviral activity against Herpes simplex virus type 1 in neuron-enriched trigeminal ganglia cultures (2014)
Herpes simplex virus type 1 (HSV-1) causes a lytic infection in epithelial cells before being captured and moved via retrograde axonal transport to the nuclei of the sensory neurons of the trigeminal ganglion or dorsal root, where it establishes a latent infection. HSV-1 infection induces an antiviral response through the production of Beta Interferon (IFN-β) in infected trigeminal ganglia. The aim of this work was to characterize the response induced by IFN-β in neuron-enriched trigeminal ganglia primary cultures infected with HSV-1. An antiviral effect of IFN-β in these cultures was observed, including reduced viral production and increased cell survival. In contrast, viral infection significantly decreased both double stranded RNA dependent protein kinase (Pkr) transcription and Jak-1 and Stat-1 phosphorylation, suggesting a possible HSV-1 immune evasion mechanism in trigeminal cells. Additionally, HSV-1 infection upregulated Suppressor of Cytokine Signaling-3 (Socs3) mRNA; upregulation of socs3 was inhibited in IFN-β treated cultures. HSV-1 infection increased the number of Socs3 positive cells and modified the intracellular distribution of Socs3 protein, in infected cells. This neuron-enriched trigeminal ganglia culture model could be used to elucidate the HSV-1 viral cycle in sensory neurons and to study cellular antiviral responses and possible viral evasion mechanisms that underlie the choice between viral replication and latency.